Studies On Pathogenic Bacteria And Physico-Chemical Parameters Of Penaeus Monodon Culture Ponds - T. SENTHIL KUMAR,; A. AMSATH,; S.S. JAYARAJ,; R. RAVICHELVAN, (International Journal of Pharma and Bio Sciences, 2012)
The bacterial species were isolated from the infected Penaeus monodon intestinal sample. Bacterial colonies were investigated from the infected P. monodon collected from coastal area at Mallippattinam, from April 2008 to September 2008. The isolated bacterial species were Echerrichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Vibrio cholerae, Enterococcus pseudoavium, Brucella canis and Aeromicrobium erythreum. Gram staining, motility test and bio-chemical test methods were used for identification of bacterial species. The physico-chemical studies revealed that high level of temperature, pH and calcium, which are the important parameters, may be responsible for the mortality of shrimps.